THE USE OF THE PRINCIPLES PHILOSOPHICAL OF JUDO IN DAILY OF JUDO PLAYERS OF RIO DE JANEIRO (Fiep Bulletin - online, 2011)
The aim of this study was identify the knowledge of the Judo's Principles by the Judo players and how they apply this in their life. On this research, 13 (thirteen) judo players participated, being 6 (six) male and 7 (seven) females. They were champions on Carioca 2010 Championship, occurred in Deodoro, Rio de Janeiro. All athletes who participated on this study practiced judo, for at least 5 (five) years, allowing us to declare that the sample were composed by people with a considerable knowledge level about this sport. The measurement was made by a valid questionnaire, composed by open and closed questions. Through answers to questions it was concluded that the sample is aware of the philosophy of judo, but mostly have not expressed in the research principles and maxims proposed by Jigoro Kano, and summarized them in terms and words that can express concept passed by the founder of judo. However, although the study has provided some evidence that these principles are present in everyday life of respondents, can not be said that this philosophy has been built exclusively for practicing the sport or whether external factors such as common sense, contributed to the understanding of values judo.
Keywords: judô; philosophical principles of judô and maxims of judô